CHINESE TRADITIONAL CREMATORIUM - Sibarani, Paterson HP; Lubis, Syamsulsyah; Sari, Juliana (Universitas Ibn Khaldun Bogor, 2021)
As time goes by, the human population and mortality rates continue to increase. The population that is increasing is inversely proportional to the amount of land as a place of settlement, causing a serious problem. The same thing happens due to the increasing number of deaths every year, the lack of land that can be used as a burial place. This can be seen from the amount of land that has shifted from its function, so people often prefer practical methods such as cremation or corpses to reduce the impact of excessive land use.